Loss of Soil Organic Matter, Lignocellulose and Microbial Population in Oil Palm Plantations Located at Different Slopes - Rika Andriati Sukma Dewi; Lilik Tri Indriyati; Bandung Sahari; Supiandi Sabiham (UNIVERSITY OF LAMPUNG, 2017)
Loss of soil organic matter can be caused by erosion triggered by soil compaction and high rainfall. The aims of the study were to determine (1) the loss of soil organic matter, lignocellulose, and soil microbial population due to erosion and (2) the contribution of organic matter from oil palm fronds. In the current study, the erosion plots were built on the accessible inter-row (gawangan hidup) and inaccessible inter-row (gawangan mati) of oil palm plantations located at the slope of 6-10% and >10%. Soil organic matter, lignin, cellulose, and hemicellulose contents and total soil microbial populations were measured in the sediments collected from the erosion plots. The results showed that the loss of organic matter was higher in the accessible inter-row than that in the inaccessible inter-row. The addition of lignin, cellulose, and hemicellulose from oil palm fronds into the soil are 2.06 Mg ha-1 yr-1, 1.13 Mg ha-1 yr-1 and 1.02 Mg ha-1 yr-1, respectively. Total bacterial population in the sediments taken from the accessible inter-row was higher than that from the inaccessible inter-row, while the total fungal population in the sediments from the inaccessible inter-row was higher than that from the accessible inter-row.